2004
DOI: 10.1088/0268-1242/19/8/017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of tin oxide microfibres electrospun from a simple precursor solution

Abstract: Tin oxide (SnO 2 ) microfibres in the rutile structure were synthesized using electrospinning and metallorganic decomposition techniques. Fibres were electrospun from a precursor solution containing 20 mg poly(ethylene oxide) (molecular weight 900 000), 2 ml chloroform and 1 ml dimethyldineodecanoate tin, and sintered in the air for 2 h at 400, 600 and 800 • C, respectively. Scanning electron microscopy, x-ray diffraction and Raman microspectrometry were used to characterize the sintered fibres. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…[1][2][3][4][5][6][7] However, for many applications such as the line light source or dielectric waveguide, the fiber morphology is more favorable. Unfortunately, so far only a few ways, such as thermal decomposition, 8 template and oxidization, 9 laser ablation or vapor-liquid-solid growth, 10 vapor deposition, 11,12 and electrospinning, [13][14][15] have been developed to fabricate SnO 2 nanofibers or ribbons. Their optical and optoelectronic properties have been only barely touched [10][11][12][13] even though such property characterization is indispensable for their optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, for many applications such as the line light source or dielectric waveguide, the fiber morphology is more favorable. Unfortunately, so far only a few ways, such as thermal decomposition, 8 template and oxidization, 9 laser ablation or vapor-liquid-solid growth, 10 vapor deposition, 11,12 and electrospinning, [13][14][15] have been developed to fabricate SnO 2 nanofibers or ribbons. Their optical and optoelectronic properties have been only barely touched [10][11][12][13] even though such property characterization is indispensable for their optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…20 A precursor solution containing dimethyldineodecanoate tin, poly͑ethylene oxide͒/water, and chloroform was used to electrospin SnO 2 microfibers. 21 Porous SnO 2 nanobelts have been fabricated by electrospinning and subsequent calcinations in air at various temperatures above 500°C. 22 In this letter, we investigate electrospun SnO 2 /MWCNT nanofibers for room temperature detection of carbon monoxide gas.…”
mentioning
confidence: 99%
“…A homogeneous precursor solution with appropriate rheological properties was made from commercial poly (ethylene oxide) (molecular weight 900 000), chloroform, and dimethyldineodecanoate tin in a pertinent ratio. Single precursor fibers were electrospun from the solution using a homemade electrospinning setup [7] onto single-crystal silicon wafers with their surface thermally oxidized and patterned with gold contacts. The as-deposited precursor fibers on the substrates were subsequently isothermally decomposed at 600 in air for 2 h, and finally gold wires were bonded to the contacts, as schematically shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1(b). Our previous characterization showed that the synthesized nanofibers were rutile-structured [7], [8]. The sensor was tested at room temperature, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation